Wheat flour as dietary fiber on fresh and preserved beef meatballs - Jamaly, SI; Hashem, MA; Akhter, S; Hossain, MA (Bangladesh Journal of Animal Science, 2017)
Effects of different levels of wheat flour as dietary fiber on the quality of fresh and preserved beef meatballs during storage were explored in this study. Ground beef (Batter) samples were divided into four treatment groups and treated with different level of wheat flour as T1 (control, 0%), T2 (5%), T3 (10%) and T4 (15%). Proximate analysis (dry matter, ash, ether extract and crude fat), sensory tests (color, flavor, tenderness, juiciness, overall acceptability), biochemical analysis (free fatty acids, Thiobarbutiric acid values and peroxide value) and microbiological examination were carried out as responses at the interval of 0, 30 and 60 days during storage at -200C. The experimental design was a 4 × 3 factorial in Completely Randomized Design replicated three times per cell. DM content was increased significantly (p<0.05) with the advancement of storage intervals. CP and EE content of all the treatments were decreased significantly (p<0.05) among the different treatment groups. FFA and TBARs values were differed significantly (p<0.05) at different treatment levels. PVs were decreased significantly (p<0.05) at different treatment levels. Color, cooking loss and overall acceptability were differed significantly (p<0.05) at different treatment levels. Raw and cooked pH were increased significantly (p<0.05) at different treatment levels. The juiciness at different treatment levels were decreased significantly(p<0.05).TVC (logCFU/g), TCC (logCFU/g) and TYMC (logCFU/g) were differed significantly (p<0.05) at different treatment levels. In conclusions, meatballs having 5% wheat flour was better in terms of color, odor, tenderness, juiciness and overall acceptability, cooking loss and microbial qualities. Bang. J. Anim. Sci. 2017. 46 (1): 35-43